The Marital Rape Based on Contemporary Islamic Criminal Law - Nimah, Rodhotun (Islamic Criminal Law Study Program, Faculty of Sharia and Law, Sunan Ampel State Islamic University Surabaya, Surabaya, East Java, Indonesia., 2023)
This research focuses on the relevance of the marital rape criminal sanction contained in Regulation Number 23 of 2004 concerning the Elimination of Domestic Violence with Criminal Sanctions in Fiqh Jinayah. This research is library research using the method of comparative legal interpretation (comparative). The type of research used is qualitative research. The legal materials used are primary legal materials in the form of classic and contemporary books as well as secondary legal materials in the form of books related to marital rape, as well as legal science journals. The data collection technique in this study is documentation. The data analysis used in this study uses Abdul Qadir 'Audah's'' analysis of thought. In this study, two conclusions were obtained, namely, that, according to Islamic law, marital rape is not in accordance with the teachings of Islamic law because Islam has taught procedures and behaviors in husband-wife relations that must be muasyarah bil ma'ruf by not hurting each other. Second, when viewed from the perspective of Abdul Qadir Audah's fiqh jinayah, the sanctions contained in the PKDRT Law have relevance to criminal sanctions in Islamic law.